2015
DOI: 10.1101/024620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation of Chromosomal Domains in Interphase by Loop Extrusion

Abstract: SUMMARYTopologically associating domains (TADs) are fundamental structural and functional building blocks of human interphase chromosomes, yet the mechanisms of TAD formation remain unclear. Here, we propose that loop extrusion underlies TAD formation. In this process, cis-acting loop-extruding factors, likely cohesins, form progressively larger loops but stall at TAD boundaries due to interactions with boundary proteins, including CTCF. Using polymer simulations, we show that this model produces TADs and fine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
593
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(635 citation statements)
references
References 76 publications
38
593
0
3
Order By: Relevance
“…Recent simulation studies have shown that although formation of a 30Kb chromatin loop can facilitate intra-loop interactions, insulation of the loop interior from the exterior is very modest with about 30% reduction in the contact frequency Benedetti et al, 2014; Doyle et al, 2014). Polymer simulations (Fudenberg et al, 2015) have also shown that even a bulky protein assembly on a chromatin fiber cannot serve as a reliable insulator providing no insulation beyond the size of the bulky assembly. Similarly, local changes in the flexibility of the chromatin fiber that can be induced by an insulator cannot provide robust insulation between regions distant from the insulator along the genome (Fudenberg et al, 2015).…”
Section: Physics Of Chromosomal Communicationmentioning
confidence: 99%
“…Recent simulation studies have shown that although formation of a 30Kb chromatin loop can facilitate intra-loop interactions, insulation of the loop interior from the exterior is very modest with about 30% reduction in the contact frequency Benedetti et al, 2014; Doyle et al, 2014). Polymer simulations (Fudenberg et al, 2015) have also shown that even a bulky protein assembly on a chromatin fiber cannot serve as a reliable insulator providing no insulation beyond the size of the bulky assembly. Similarly, local changes in the flexibility of the chromatin fiber that can be induced by an insulator cannot provide robust insulation between regions distant from the insulator along the genome (Fudenberg et al, 2015).…”
Section: Physics Of Chromosomal Communicationmentioning
confidence: 99%
“…The extrusion model is favored. It proposes that DNA is actively extruded through cohesin rings until reaching two compatible roadblocks that stabilize the thereby formed chromatin loop (Fudenberg et al 2015;Sanborn et al 2015). For roadblocks to be compatible, it is assumed that CTCF molecules must be bound in a convergent orientation.…”
Section: Ctcf-and Cohesin-mediated Architectural Loops Surrounding Tadsmentioning
confidence: 99%
“…3). This is an attractive model because its geometry gives rise to exactly the kind of (largely) nonoverlapping pattern of loop domains observed in vivo as well as the intraloop folding patterns deduced from the Hi-C data (Rao et al 2014;Fudenberg et al 2015;Sanborn et al 2015;Dekker and Mirny 2016). Theory and experiment do not necessarily agree in detail, possibly a reflection of the ways in which evolution has elaborated on simple polymer physics.…”
Section: Mechanisms For Generating Convergencementioning
confidence: 99%